Dormancy and germination in two Australian native species (Acacia aneura and Rhodanthe floribunda) - Paul Theophile Epee Misse* (African Journal of Biological Sciences, 2019)
In the laboratory of plant physiology of the University of Queensland (Gatton Campus), a seed germination experiment was undertaken on seeds of two Australian native plant species – Rhodanthe floribundato and Acacia aneura. Most Acacia, including A. aneura exhibit a physical dormancy due to the waxy coat covering the seed. Comparably, just a few species of Rhodanthe are studied as to their dormancy. However, they are also known to present different forms of dormancy. To understand and describe these dormancy mechanisms, a seed germination experiment was conducted on Acacia aneura and Rhodanthe floribunda. This experiment will either add to the existing knowledge regarding these species’ dormancy or corroborate them. It is expected that both species display some form(s) of dormancy.
Keywords: Germination, Rhodanthe floribundato, Acacia aneura, Physical dormancy